2019
DOI: 10.1186/s13071-019-3852-6
|View full text |Cite
|
Sign up to set email alerts
|

A review on the eco-epidemiology and clinical management of human granulocytic anaplasmosis and its agent in Europe

Abstract: Anaplasma phagocytophilum is the agent of tick-borne fever, equine, canine and human granulocytic anaplasmosis. The common route of A. phagocytophilum transmission is through a tick bite, the main vector in Europe being Ixodes ricinus. Despite the apparently ubiquitous presence of the pathogen A. phagocytophilum in ticks and various wild and domestic animals from Europe, up to date published clinical cases of human granulocytic anaplasmosis (HGA) remain rare compared to the worldwide status. It is unclear if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 137 publications
2
101
1
2
Order By: Relevance
“…Other Anaplasma species such as A. platys, A. centrale, A. marginale has not been detected in roe deer. All AP isolates obtained in this study were qualified to a single ecotype, differing from the AP ecotypes found in humans, farm animals and domestic animals, as well as from those isolated from rodents, which may indicate that the roe deer in eastern Poland do not constitute a reservoir host for the human pathogenic strains of AP [36].…”
Section: Aaem Annals Of Agricultural and Environmental Medicinementioning
confidence: 71%
“…Other Anaplasma species such as A. platys, A. centrale, A. marginale has not been detected in roe deer. All AP isolates obtained in this study were qualified to a single ecotype, differing from the AP ecotypes found in humans, farm animals and domestic animals, as well as from those isolated from rodents, which may indicate that the roe deer in eastern Poland do not constitute a reservoir host for the human pathogenic strains of AP [36].…”
Section: Aaem Annals Of Agricultural and Environmental Medicinementioning
confidence: 71%
“…These increases are partially explained by geographical spread of its vector, Ixodes ricinus [4,5]. Other tick-borne diseases (TBDs), such as anaplasmosis and neoehrlichiosis, are also emerging [6,7]. Understanding which factors drive the population densities of ticks and the transmission cycles of tick-borne pathogens are important steps in assessing disease risk and formulating possible intervention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…One of the answers could be the high genetic diversity of the European A. phagocytophilum strains, which could be a consequence of adaptation of A. phagocytophilum to different host species. Circulation of four A. phagocytophilum ecotypes has been established, and it is known that ecotype/ cluster (I) is isolated significantly more often from dogs than the other ecotypes (Matei et al, 2019;Jahfari et al, 2014).…”
Section: Borrelia Burgdorferi Sensu Lato (Sl) Complexmentioning
confidence: 99%